الوعي بالأمن السيبراني لدى معلمي المرحلة المتوسطة بدولة الكويت وعلاقته بمستوى توظيفهم للتكنولوجيا في التدريس - الضفيري، ناجي بدر; العنزي، إبراهيم غازي; العنزي، دلال فرحان نافع (مركز العطاء للإستشارات التربوية, 2024)
هدف البحث الحالي إلى الكشف عن مستوى الوعي بالأمن السيبراني ومستوى توظيف التكنولوجيا في التدريس لدى عينة من معلمي المرحلة المتوسطة بالكويت. وتم استخدام المنهج الوصفي المسحي، واشتملت العينة على (124) من معلمي ومعلمات المرحلة المتوسطة بمنطقة العاصمة. وتم جمع البيانات باستخدام اختبار الوعي بالأمن السيبراني من إعداد "جين-بيري" (Jean-Pierre, 2021)، واستبانة توظيف التكنولوجيا في التدريس من إعداد الباحثين. وأوضحت النتائج أن مستوى الوعي بالأمن السيبراني لدى المعلمين لا يرتقي إلى مستوى الإتقان، وعدم وجود فروق ذات دلالة إحصائية في مستوى الوعي بالأمن السيبراني تعزى لمتغيري النوع وعدد سنوات الخبرة، بينما توجد فروق تعزى لمتغير التخصص لصالح معلمي التخصصات العلمية والعملية، كما بينت النتائج وجود مستوى متوسط من توظيف التكنولوجيا في التدريس لدى المعلمين؛ إذ بلغ المتوسط الحسابي العام للاستبانة (2,62) واتضح عدم وجود فروق ذات دلالة إحصائية في مستوى توظيف التكنولوجيا في التدريس تعزى لمتغيري النوع وعدد سنوات الخبرة في التدريس، بينما كانت هناك فروق تعزى للتخصص لصالح معلمي التخصصات العلمية والعملية (الرياضيات، العلوم، الحاسب الآلي، الكهرباء)؛ وأظهرت النتائج وجود علاقة ارتباطية موجبة دالة إحصائيا بين الوعي بالأمن السيبراني وتوظيف التكنولوجيا في التدريس، ووجود تأثير دال لمستوى الوعي بالأمن السيبراني على توظيف التكنولوجيا في التدريس لدى معلمي المرحلة المتوسطة بدولة الكويت. The current research aimed to reveal the level of awareness of cybersecurity and the level of technology integration in teaching among a sample of middle school teachers in Kuwait. The descriptive survey method was used, and the sample included (124) middle school teachers in the capital region. Data were collected using a cybersecurity awareness test prepared by Jean-Pierre (2021), and technology integration questionnaire prepared by researchers. The results showed that the level of awareness of cybersecurity among teachers does not rise to the level of mastery, and that there are no statistically significant differences in the level of awareness of cybersecurity due to the variables of gender and number of years of experience, while there are differences due to the variable of specialization in favor of teachers of scientific and practical specializations. The results also showed that there is a moderate level of technology integration in teaching among teachers; with a general mean of (2.62), and that there were no statistically significant differences in the level of technology integration in teaching due to the variables of gender and the number of years of teaching experience, while there were differences due to specialization and in favor of teachers of scientific and practical specializations (mathematics, science, computer and electricity); the results showed that there is a positive, statistically significant correlation between awareness of cybersecurity and technology integration in teaching, and the presence of a significant effect of the level of awareness of cybersecurity on the technology integration in teaching among middle school teachers in the State of Kuwait.
Keywords: التواصل الرقمي -- الفضاء السيبراني -- الوعي المعلوماتي -- تكنولوجيا المعلومات